(untitled) (Journal of Oriental Studies, 2016)
In the article Various parties of female inequality (old consuetude, solitary life of girls, repayment for the bride are covered in article...) in the Arab novel, and also interest of modern writers in children’s subject which is caused by sharp requirement to change social conditions of a life of young people, to promote education of the younger generation in the spirit of patriotism, etc.